Reviews (Blackfriars, 1934)
catholic action: Petit Catechisme de L'Action Catholique. Mgr. Fontenell. Brief Catechism of Catholic Action. Rt. Rev. Mgr. R. Fontenelle. catholic action: L'Action Catholique. Essal de synthése. Paul Dabin, S.J. catholic action: L'Apostolat Laique. Paul Dabin, S.J. catholic action: Code de L'Action Catholique. A. Guerry. catholic action: Rome et L'Action Catholique. P. Romain. catholic action: L'Action Catholique. Traduction française des documents pontificaux, 1922–1933. catholic action: Tu es Petrus. (Bloud et Gay; 60 francs.) religion and philosophy: Precis de Patrologie et d'Histoire de la Theologie. By F. Cayrée. religion and philosophy: Notre-Dame a Nazareth. (Editions du Cerf, Juvisy). religion and philosophy: Sur le Devoir D'Imprévoyance. By Isabelle Riviére. religion and philosophy: En lisant les Peres. By G. Bardy. religion and philosophy: Das Seelenleben des Menschen, Eine Eünfuhrung in die Psychologie. By Johannes Lindworsky. drama and fiction: The Rock. By T. S. Eliot. drama and fiction: Thomas Mann. By James Cleugh. drama and fiction: The Tales of Tacos. By Thomas Mann. drama and fiction: The Lost Hero. By Robert Speaight. drama and fiction: Seed of Adam. By Violet Campbell. social and political: Civitas Dei. By L. Curtis. social and political: The Tragedy of a Nation. By Prince Hubertus Loewenstein social and political: Christianity and Internationalism. By John Nibb.